UJI DIFUSI MIKROEMULSI NITROGLISERIN MENGGUNAKAN TWEEN 80 SEBAGAI SURFAKTAN - Yati, Kori; Situmorang, Almawati; Umoro, Ani (Jurnal Farmasi Indonesia, 2017)
ABSTRACT: Nitroglycerine is a drug of choice in the treatment of angina pectoris. Nitroglycerine has low dose, short time of plasma half life and liver metabolizing. This study used the formulation of microemulsion. The advantages of microemulsion transparent form, stable and has better skin penetration due to the smaller size of its droplet. This study aims at determining concentration of Tween 80 as surfactant as penetration in the nitroglycerine microemulsion. Tween 80 concentrations used were 40% (F1), 42,5% (F2) and 45% (F3). Penetration ability was tested by invitro using Franz diffusion cells. The results showed that 42,5% of the concentration of Tween 80 produces good penetration. F2 shows the measurement result of droplet size is 69,0 nm and diffusion test on the minutes of 180 for 86,00% Â± 3,65. It can be concluded that the concentration of Tween 80 as surfactant of 42,5% gives microemulsion nitroglycerine with good penetration.